Building Positive Mental Resilience for Santri - azam syukur rahmatullah; Muhammad Eko Atmojo (At-Tarbiyat, 2022)
This study aims to discover what and how to develop positive mental resilience at Madrasah Diniyyah Puteri Padang Panjang, West Sumatra. Even though all the santri are female, they are still equipped with endurance, mentality, self-strength, and struggle tips. Madrasah Diniyyah Puteri Padang Panjang continues to provide mental-based programs. Hence, the santri can later stand on their feet and become messengers of goodness and virtue for the wider community. This research is naturalistic qualitative research and uses an ethnomethodological approach. The research subjects were selected and randomized using a purposive sampling technique with a snowball model. The results showed that female students’ resilience at Madrasah Diniyyah Padang Panjang, West Sumatra, has essentially been based on a solid foundation by Rahmah El Yunusiyyah. A reliable mental education forerunner is then sown to the next generation yearly. The mental character remains strong and thrives. Several factors leading to this resilience were presented, grounded, and propagated in Madrasah Diniyyah Padang Panjang, West Sumatra; first, preserving the ancestral heritage; second, the factors of mental regeneration of women; third, the characteristics for degrading women by irresponsible persons. The programs for female students were: A Good Leader Program, Super Santri Camp Program, Dream Realization Program, Santri Pledge Program, and Character Survey Program, Room Shifting Program.